VOCATIONAL MASTERS TRANING IN THE CONTEXT OF GROWING SOCIAL AND PROFESSIONAL MOBILITY - Alexandr G. Kislov (Russian State Vocational Pedagogical University, 2015)
The study is aimed at investigating the trends of vocational training development reflecting the demands of changing professional world.Methods: The applied methods include historic, genetic and socio-context analysis of the current developments in vocational training sphere.Results: The research findings prove the priority of meta-professional and meta-competency landmarks in vocational masters training.Scientific novelty: The author points out the lagging behind of the Federal State Educational Standard and corresponding vocational training programs compared to the fast growing social and professional mobility. The paper emphasizes the urgent need for vocational pedagogical education as a part of vocational training at all levels - the secondary, higher and postgraduate.Practical significance: The research outcomes can be used for further development of conceptual, methodological, organizational and contextual bases of vocational masters training.